(untitled) (Південний архів (історичні науки), 2025)
The aim of this study is to analyze the actions of the Russian authorities concerning deliberate destruction of the educational infrastructure of the South of Ukraine including repressive measures against Ukrainian teachers and scholars, russification, indoctrination of school and university students in the occupied territories, targeted destruction of educational institutions through shelling, and the looting of their property. Methods. The author of this article employs analytical method to analyze publications in mass media, reports from human rights organizations, official documents, interviews with internally displaced people, content analysis to study texts of propaganda materials disseminated among students by the Russian authorities, a comparative method during comparison of the modern state of the Ukrainian education in Southern Ukraine and with its state in pre-war conditions, and a historical method to analye the prerequisites and chronology of educational changes in the occupied territories. The sociological method was used to study the reactions of students, teachers, parents to the forced implementation of the Russian education system. The statistical method was applied for data collection and its analysis. Results. The article analyzes how Russian state authorities have destroyed the educational environment of the South of Ukraine from 2022 to 2024 on the basis of testimonies of internally displaced people as an element of Russia’s occupation policy against the Ukrainian nation. Conclusions. The author claims that shelling of educational infrastructure by Russian militaries is deliberate. Indoctrination, russification and deportation of Ukrainian children and youth form a systematic policy and are part of the genocide against Ukrainians. Educators and scholars in the occupied territories of the South of Ukraine face severe repressions for their pro-Ukrainian stance. The actions of Russia’s military-political leadership against Ukraine’s educational environment in Southern Ukraine violate numerous international legal norms.